The Therapeutic Mechanisms of Honey in Mitigating Toxicity from Anticancer Chemotherapy Toxicity: A Review - Debalina Bose; Ademola C. Famurewa; Aman Akash; Eman M. Othman (Journal of Xenobiotics)
Within the domain of conventional oncochemotherapeutics, anticancer chemotherapy (AC) has emerged as a potent strategy for the treatment of cancers. AC is the mainstay strategy for solid and non-solid cancer treatment. Its mechanistic action targets the blockage of DNA transcription and the dysregulation of cell cycle machinery in cancer cells, leading to the activation of death pathways. However, the attendant side effect of toxicity inflicted by AC on healthy tissues presents a formidable challenge. The crucial culprit in the AC side effect of toxicity is unknown, although oxidative stress, mitochondrial impairment, inflammatory cascades, autophagy dysregulation, apoptosis, and certain aberrant signaling have been implicated. Honey is a natural bee product with significant health benefits and pharmacological properties. Interestingly, the literature reports that honey may proffer a protection mechanism for delicate tissue/organs against the side effect of toxicity from AC. Thus, this review delves into the prospective role of honey as an alleviator of the AC side effect of toxicity; it provides an elucidation of the mechanisms of AC toxicity and honey’s molecular mechanisms of mitigation. The review endeavors to unravel the specific molecular cascades by which honey orchestrates its mitigating effects, with the overarching objective of refining its application as an adjuvant natural product. Honey supplementation prevents AC toxicity via the inhibition of oxidative stress, NF-κB-mediated inflammation, and caspase-dependent apoptosis cascades. Although there is a need for increased mechanistic studies, honey is a natural product that could mitigate the various toxicities induced by AC.